2019
DOI: 10.1002/cam4.2238
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between muscle mass and handgrip strength in digestive cancer patients undergoing chemotherapy

Abstract: Background FIGHTDIGO study has shown the feasibility of handgrip strength (HGS) measurements in 201 consecutive digestive cancer patients undergoing chemotherapy. Objective This study focuses on a secondary aim of FIGHTDIGO study: the relationship between muscle mass and HGS. Design Two consecutive bilateral measures of HGS were performed using a Jamar dynamometer before the start of each chemotherapy. The highest value was chosen for final e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 49 publications
6
27
0
Order By: Relevance
“…A correlation between ASMI and HGS has recently been described in sarcopenia due to cancer-cachexia [ 47 ]. In agreement with those results, we found a significant association between muscle atrophy and dynapenia in COPD participants.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between ASMI and HGS has recently been described in sarcopenia due to cancer-cachexia [ 47 ]. In agreement with those results, we found a significant association between muscle atrophy and dynapenia in COPD participants.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer patients, lower HGS values are associated with unfavorable clinical outcomes, such as longer hospital stays, poor quality of life, postoperative complications and mortality [33,36,50]. However, the measure is still seldom used in hospital and outpatient clinical practice, as there are no specific cutoff points for cancer patients and for the evaluation of reduced HGS values in non-elderly subjects [39,50].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed a correlation between HGS and the SARC-CalF score. Moreau et al (28), when studying patients with GIT cancer, demonstrated a strong correlation between the measurement of HGS and muscle mass. Of the 150 patients evaluated by these researchers, 80 % showed loss of muscle mass and strength, with a consequent progression to sarcopenia.…”
Section: Resultsmentioning
confidence: 95%